Ecotoxicological hazards of sea star-derived asterosaponins: mechanistic insights into embryotoxicity and cardiotoxicity in marine medaka - Ranran Zhang; Zhen Lu; Derui Wang; Zhi Yan; Xueting Sun; Xiaodong Li; Xiuli Yin; Ke Li (Ecotoxicology and Environmental Safety)
Outbreaks of the sea star in northern China Sea, supported by its robust chemical and physical defenses, have disrupted marine ecological balance and caused substantial economic losses to aquaculture. To investigate the compounds responsible for its chemical defense, three asterosaponins (SP1–SP3) and their shared aglycone (AG) were isolated and identified. The embryotoxicity of these compounds was evaluated using marine medaka embryos (Oryzias melastigma), with 96 h-LC50 values determined as 76.05, 2.84, 1.35, and 4.08 μM for AG, SP1, SP2, and SP3, respectively. The structure-toxicity relationship revealed that steroidal glycosides exhibited higher toxicity than their aglycone counterparts. Additionally, the composition and linkage patterns of the saccharide chains significantly influenced embryotoxicity. Transcriptomic analysis uncovered pronounced activation in pathways, including those involved in adrenergic signaling within cardiomyocytes, cardiac muscle contraction, calcium-mediated signaling, and neuroactive ligand-receptor interactions. Biochemical assays demonstrated decreased Na+ /K+-ATPase activity and reduced myosin light chain kinase (MLCK) levels in treated groups, aligning with the down-regulation of the atp1b4 and mylkb genes. These findings indicate that asterosaponins and their aglycone induce cardiotoxicity in marine medaka embryos, contributing to the foundation for further chemical ecological research and acute environmental hazard assessment.